PENJADWALAN ULANG KAPAL REPARASI TB. PATRA TUNDA 3001 DENGAN METODE JALUR KRITIS - Maharani Rosa Meinanda Istiqomah; Imam Pujo Mulyatno; Sarjito Joko Sisworo; Eko Sasmiton Hadi; Kiryanto Kiryanto; Ocid Mursid (Jurnal Teknologi Perikanan dan Kelautan, 2021)
Scheduling in the repair process is often not according to the initial planning in the main schedule of the ship. Delays in a new shipbuilding project or ship repair will cause losses that have an impact on many parties; both the shipyard, the owner and third parties. To minimize the occurrence of delays, one effective way is to accelerate with a Critical Path Method. The research object selected is ship repair TB. Patra Tunda 3001. The purpose of this research is to get a new duration after rescheduling ship repair, find work activities on the critical path, get the value of labor productivity, and find the most optimal time and cost to speed up the duration of the project with crashing through the comparison of two alternatives, namely the addition of working hours (overtime) and additional human resources. The total normal cost is Rp 9,360,000. From the data processing analysis, it was concluded that the addition of working hours (overtime hours) and the addition of labor showed the same optimal acceleration with a 25% result, which was 4 days earlier than the total project normal duration of 16 days. There is a cost difference of 39.31% greater than the normal duration with the alternative of additional working hours (overtime hours) and the difference in cost reduction of 27.35% which is smaller than the normal duration with the alternative of additional manpower. Reschedule for ship repair TB. Patra Tunda 3001 with the addition of labor is more efficient and optimal work.